OFR-146(2)-77 Comparative Coal Transportation Costs: An Economic And Engineering Analysis Of Truck, Belt, Rail, Barge And Coal Slurry And Pneumatic Pipelines - Volume 2 ? Unit Trains ? 2.1 Introduction - Michael Rieber (The National Institute for Occupational Safety and Health (NIOSH), 1977)
The increase in f.o.b. mine prices of coal from $5/ton to over $18/ton in five years [1] has increased the significance of transportation costs. Coals produced in the vicinity of the consumer bear a much lower transport cost than those produced in the west. This differential may be used for flue gas desulfurization, other cleaning, or further processing of local coals. To the extent that western coals are cheaper to produce and have a lower sulfur content, they offset the locational disadvantage. To the extent that they have a lower heating value, the disadvantage is exercabated. Given the other conditions, an accurate analysis of transport costs will help suggest the location of coal mining and the moue of transport both transport costs and tariffs have risen. Together they have increased delivered coal prices, altered the balance between the use of coal and other fuels, helped to alter the location of mining activity, and put pressure on consumers to examine the cost effectiveness of alternative transport modes. Transportation options for long distance coal movements include rail, barge, pipeline, and EHV transmission lines. A summary of system parameters is shown in Table 2.1. Barge transport, pneumatic and slurry pipelines are discussed elsewhere in this report. Together with EHV, they have been the subject of previous studies [2,3,4]. Slurry pipelines have been shown to be especially useful where rails are not available [2] but the technical problems of dewatering, handling, and utilization of lines [5] remain unresolved. They are discussed in Section 3. Barge transportation depends on the location of the mine and consumer with respect to the waterway system. One drawback of barge shipment is interruptions due to winter, and low or high water conditions. Mine mouth power generation followed by EHV transmission of over 500 miles has been shown to be the most expensive means of delivering an equivalent amount of energy to consumers [2].